Catalytic co-pyrolysis of polycarbonate and polyethylene/polypropylene mixtures: Promotion of oil deoxygenation and aromatic hydrocarbon formation. (1st February 2021) - Sun, Kai; Wang, Wanli; Themelis, Nickolas J.; Thanos Bourtsalas, A.C.; Huang, Qunxing
Graphical abstract: Highlights: Deoxygenation of PC pyrolysis oil was achieved by catalytic co-pyrolysis. Dehydrogenation of PP and hydrodeoxygenation of PC can be simultaneously catalyzed. High value-added aromatics were the target products of all reactants. The content of oxygenates in oil reduced to 2.9% when PC: PP was 25 wt%:75 wt%. The content of bicyclic aromatic hydrocarbons like naphthalenes could be up to 54.5%. Abstract: The co-pyrolysis of polycarbonate (PC) and polyethylene (PE)/polypropylene (PP) in the presence of HZSM-5 catalyst was studied in a two-stage tube reactor with the objective of promoting simultaneous deoxygenation and aromatic hydrocarbon formation, at atmospheric pressure and without external hydrogen addition. As the blending ratio of PE/PP increased, the yield of oil phase product, coke, and solid decreased, and the yield of gas phase increased significantly. At the blending ratio of 75% PP, the concentration of oxygenates in the oil was reduced to 2.9% and that of aromatic hydrocarbons increased to 97.1%. Increasing the reaction temperature from 500 °C to 700 °C increased the yield of aromatic hydrocarbons further to 98.1%. Catalyst regeneration decreased the acidity of the HZSM-5 catalyst, resulting in a slight decrease in the deoxygenation and aromatization effects. The results showed that PP is an effective hydrogen donor in the catalytic deoxygenation and aromatization process; the hydrogen provided enhanced the adsorption of phenols produced by the pyrolysis of PC on HZSM-5 and their direct deoxygenation to form new aromatic hydrocarbons.